Study of socio-demographic determinants and body mass index of female class IV employees (Aayas and Mehatranis) at a municipal tertiary care teaching hospital in Mumbai, India - Gawari, Bhagyashri D.; Lavangare, Sujata R.; Velhal, Gajanan D. (International Journal Of Community Medicine And Public Health, 2019)
Background: Health care professionals (including class IV employees) are the most ignorant as far as their own health is concerned. Problems encountered at the workplace affect not only a worker’s health but also adversely affects the workplace environment. Today is an era of women who have diverse role to play in the society and often they handle multiple tasks simultaneously. They are therefore prone to suffer from work related diseases, which are further complicated by various social (responsibilities at home), psychological and physiological (e.g., pregnancy) issues. Methods: A cross-sectional study was carried out amongst 287 female class IV employees of municipal tertiary care teaching hospital in Mumbai during the period of April 2017 to December 2018. A semi-structured interview schedule was prepared comprising of socio-demographic determinants and BMI. Data was entered in MS Excel sheet and were analyzed in the form of percentage and proportions whenever necessary. Results: Out of total 287 participants, 101 (35.2%) belonged to age group of 41-50 years, more than half 168 (58.5%) were widows and majority 231 (80.5%) were Hindu by religion, 124 (43.2%) belonged to upper middle class, 158 (55.0%) belonged to a nuclear family and 44 (15.3%) had to travel more than 60 kms daily to reach at workplace. Conclusions: Study concluded that 35.2% participants were 41-50 years age group and 80.5% were Hindu by religion and 43.2% belonged to the upper middle class. Only 2.1% respondents had completed their graduation. More than half i.e. 55.1% of the participants were having normal body mass index and 10.5% were obese.